Artificial Intelligence in Cybersecurity Legal and Ethical Challenges in Regulating Autonomous Defense Systems - Purna Putra, Grahadi (Universitas Islam Negeri Walisongo Semarang, 2025)
The emergence of Artificial Intelligence (AI) in autonomous cybersecurity defense systems has created a profound regulatory and ethical. Current doctrines of responsibility, which center on the role of humans, are insufficient to regulate AI systems that act independently, particularly in the context of cross-border cyber incidents. This study uses a normative and comparative legal approach, examining regulatory frameworks such as the EU AI Act and Russian cyber law to assess the consequences of legal fragmentation and weak international harmonization. It shows that outdated laws do not adequately cover all aspects of fault, transparency, and fairness in AI-supported online security. The paper suggests granting legal status to computer programs and establishing ways for people to engage in the process, in addition to examining how these algorithms affect us, as a means of ensuring that they are accountable. This two-pronged approach integrates fairness, transparency, and proportionality into AI governance, while strengthening ethical oversight. Further study recommends a proportional division of responsibility among developers, distributors, and regulators, as well as international harmonization to prevent regulatory arbitrage. By integrating conceptual and practical insights, this research advances anticipatory and ethics-based governance to ensure that AI-based cybersecurity systems operate effectively while upholding human rights and global security. Kemunculan kecerdasan buatan (AI) dalam sistem pertahanan keamanan siber otonom menciptakan kekosongan regulasi dan etika. Doktrin tanggung jawab yang berpusat pada peran manusia, tidak memadai untuk mengatur sistem AI yang bertindak secara independen, terutama dalam konteks insiden siber lintas batas. Studi ini menggunakan pendekatan hukum normatif dan komparatif, mengkaji kerangka regulasi seperti undang-undang AI Uni Eropa dan hukum siber Rusia untuk menilai konsekuensi fragmentasi hukum dan harmonisasi internasional yang lemah. Studi ini menunjukkan bahwa undang-undang yang sudah ketinggalan zaman tidak mencakup semua aspek kesalahan, transparansi, dan keadilan dalam keamanan daring yang didukung AI secara memadai. Penelitian ini menyarankan pemberian status hukum kepada program komputer dan menetapkan cara bagi orang-orang untuk terlibat dalam prosesnya, selain mengkaji bagaimana algoritma ini memengaruhi kita, sebagai cara untuk memastikan akuntabilitasnya. Pendekatan bercabang dua ini mengintegrasikan keadilan, transparansi, dan proporsional ke dalam tata kelola AI, sekaligus memperkuat pengawasan etika. Studi lebih lanjut merekomendasikan pembagian tanggung jawab yang proporsional antara pengembang, distributor, dan regulator, serta harmonisasi internasional untuk mencegah arbitrase regulasi. Dengan mengintegrasikan wawasan konseptual dan praktis, penelitian ini memajukan tata kelola antisipatif dan berbasis etika untuk memastikan bahwa sistem keamanan siber berbasis AI beroperasi secara efektif sambil menjunjung tinggi hak asasi manusia dan keamanan global. Keywords: AI governance; legal liability; cybersecurity ethics.